The Anti-Allergic And Anti-Inflammatory Effect Of Fingerroot (Boesenbergia Rotunda) Rhizome Extract In Male White Wistar Rats Induced By Ovalbumin - Diah Hermayanti; Hawin Nurdiana; Alifia Salsabila Teka; Vania Nabila Putri; Yosiene Dhea Elfita (Universitas Muhammadiyah Malang, 2025)
Background: Type 1 hypersensitivity reactions are characterized by IgE elevation, cytokine release, and eosinophil recruitment leading to airway inflammation. Fingerroot rhizomes (Boesenbergia rotunda) contain flavonoids such as panduratin A with potential anti-allergic and anti-inflammatory properties.Aim: To evaluate the effect of Boesenbergia rotunda rhizome extract (BRE) on IgE, TNF-α, eosinophil counts, tissue necrosis, and alveolar cell proliferation in ovalbumin (OVA)-induced Wistar rats.Methods: Twenty-five male rats were divided into five groups: negative control, positive control, and three BRE treatment groups (350, 700, 1400 mg/kg BW). OVA was administered intraperitoneally (days 0, 7, 14) and via inhalation (days 19–22). BRE was given orally from days 15–22. IgE and TNF-α were measured by ELISA, while lung histology was assessed for eosinophils, necrosis, and alveolar proliferation.Results: BRE significantly reduced eosinophil counts, necrosis, and alveolar proliferation compared with the positive control (p < 0.05). The highest dose (1400 mg/kg) showed effects similar to the negative control. IgE and TNF-α changes were less consistent.Conclusion: BRE exhibits anti-allergic and anti-inflammatory activity in OVA-induced rats, mainly by reducing eosinophilic infiltration and lung tissue damage. It shows promise as a natural therapeutic candidate, meriting further safety and clinical studies.